Implementasi Manajemen Strategik Dalam Pengembangan Life Skill (Kecakapan Hidup) Di MTs Diponegoro Plandaan Jombang - Mokh. Fakhruddin Siswopranoto; Agus Zaenul Fitri (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Research on the implementation of strategic management in developing life skills aims to describe the implementation of strategic management at MTs Diponegoro Plandaan Jombang. The focus of this research is, among others, life skills development programs, budgets, and procedures for developing life skills. This research is qualitative with the type of field research or field research. While the data collection uses observation, interviews, and documentation. Data analysis using a descriptive analysis method. The results of this study indicate that strategic implementation which includes life skill development programs, budgets, and procedures has a positive impact on madrasa achievement and competitiveness.